Construction of a generic reference material for gamma ray spectrometric analysis - J. M. Kebwaro; N.O. Hashim; A. O. Mustapha (Institut Teknologi Bandung, 2011)
An artificial reference material (RGMIX) has been constructed from three IAEA materials (RGU-1, RGTH-1, RGK-1). The material is analogous of an environmental radioactive material. The material is systematically analysed on a NaI(Tl) detector using the method of spectrum decomposition. The spectrum of the sample is similar to that of a geological material.